Prevalensi Gen OXA-23 pada Isolat Klinis Bakter Acinetobacter baumanii di RSUP Dr. M. Djamil Padang - Mhd. Alzaref; Linosefa Linosefa; Gestina Aliska (Fakultas Kedokteran, Universitas Andalas, 2021)
Acinetobacter baumannii is such a big challenge in this modern era because of their multi-drug resistance (MDR) through their resistance mechanism, namely the production of beta lactamase enzymes, one of them is oxacillinases. Several studies have revealed that the OXA-23 gene has an important role in the production of the beta lactamase enzyme so that these bacteria are resistant to antibiotics, especially carbapenem. This study was conducted to determine the description of the resistance of the Acinetobacter baumannii by looking at the prevalence of the OXA-23 gene in clinical isolates of these bacteria at RSUP Dr. M. Djamil Padang. This study was a descriptive observational study and used a cross-sectional design using polymerase chain reactions (PCR) and electrophoresis techniques. The samples were clinical isolates of Acinetobacter baumannii bacteria stored in the Microbiology Laboratory of the Faculty of Medicine, Andalas University with inclusion and exclusion criteria. Of the 150 clinical isolates of Acinetobacter baumannii studied, most of the bacteria were still sensitive to the antibiotics of Amikacin (84%), Tigecycline (78.76%), and Trimethoprim / Sulfamethoxazole (76.77%). Meanwhile, all of the Acinetobacter baumannii isolates were resistant to cefazolin. In PCR and electrophoresis tests, 50 clinical isolates were positive for the OXA-23 gene. 46 of them were carbapenem resistant, while the other 4 isolates were sensitive to carbapenem. From these results it can be concluded that the prevalence of the OXA-23 gene in Acinetobacter baumannii isolates in RSUP Dr. M. Djamil Padang was 85.18% for carbapenem resistant isolates and 4.30% for carbapenem sensitive isolates. Keywords : Acinetobacter baumannii, carbapenem, OXA-23 gene